2006
DOI: 10.1530/eje.1.02192
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sex-steroid administration on the pituitary–thyroid axis in transsexuals

Abstract: Objective: Estrogen and androgen administration modulate the pituitary-thyroid axis through alterations in thyroid hormone-binding globulin (TBG) metabolism, but the effects of sex steroids on extrathyroidal thyroxine (T 4 ) to triiodothyronine (T 3 ) conversion in humans are unknown. Design and methods: We studied 36 male-to-female and 14 female-to-male euthyroid transsexuals at baseline and after 4 months of hormonal treatment. Male-to-female transsexuals were treated with cyproterone acetate (CA) 100 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The role of gonadal steroids in this conversion is not clear. A recent study in transsexuals showed that testosterone increased conversion of T4 to T3, while oestrogen (used with cyproterone acetate) did not have any effect on the T3/T4 ratio 21 . Growth hormone rises markedly in puberty and could play a role in this conversion because of its activation of deiodinase type 1 and type 2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The role of gonadal steroids in this conversion is not clear. A recent study in transsexuals showed that testosterone increased conversion of T4 to T3, while oestrogen (used with cyproterone acetate) did not have any effect on the T3/T4 ratio 21 . Growth hormone rises markedly in puberty and could play a role in this conversion because of its activation of deiodinase type 1 and type 2.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study in transsexuals showed that testosterone increased conversion of T4 to T3, while oestrogen (used with cyproterone acetate) did not have any effect on the T3/T4 ratio. 21 Growth hormone rises markedly in puberty and could play a role in this conversion because of its activation of deiodinase type 1 and type 2. The lack of a consistent change in TSH probably argues against any significant change in the hypothalamic-pituitary-thyroid axis.…”
Section: Discussionmentioning
confidence: 99%
“…Fat mobilization, as indicated by increased BHBA during oestrus in dairy cows, was also accompanied by greater T3 concentrations (Mohebbi‐Fani et al., ). Furthermore, the administration of estradiol has been shown to increase the concentration of T3 in women (Bisschop et al., ), which supports the increase in T3 during oestrus. Strong ties between T3 and intermediary metabolism support the key relevance of T3 as a predictor of oestrus.…”
Section: Discussionmentioning
confidence: 78%
“…We believe that his supplements contained T4, thus explaining why both T3 and T4 levels were elevated. His testosterone use may have also contributed to his thyrotoxicosis given its role in reduction of thyroid-binding globulin, potentially increasing his unbound thyroid hormone levels (8).…”
Section: Discussionmentioning
confidence: 99%